PENGARUH STRATEGI PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR MATEMATIKA - Nuralam - (JTP - Jurnal Teknologi Pendidikan, 2014)
This study aims to determine the effect of learning approaches and cognitive styles as well as its interaction with mathematics learning outcomes. This study used an experimental research 2 x 2 factorial design with 68 people were taken by cluster random sampling in madrasah tsanawiyah. The results showed that there is an interaction effect between learning and cognitive style approach to math learning outcomes. Thus the selec- tion of the relevant learning approach, the acquisition of mathematics learning outcomes are in uenced by the ability of teachers to understand the characteristics of their students. It gives the effect for students who have a particular cognitive style taught by a different learning approach gives results different learning mathematics. Learning approach applied to optimize the mathematics teacher of mathematics learning outcomes of students who have a eld independent cognitive styles.